2018
DOI: 10.5539/jas.v10n10p248
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Wastewater for Forage Cultivation in Cerrado Soil

Abstract: Fertigation of agricultural crops that are not directly used in human food, with domestic wastewater is a viable alternative for the sustainable use of water resources. The development of agricultural practices that provide high productivity with the sustainability of agroecosystems has been a great challenge. Thus, our aims were to use of domestic wastewater in the planting of Brachiaria brizantha cv Marandu, as an alternative for animal feed production in Cerrado soils, and to study the physical-chemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…Viable bacterial cells counts were higher than those of actinomycete and fungi regardless of the soybean farm, sample collection points, soil depth, and season (Tables 3 to 5). These results are similar to those obtained by Silva et al (2018) in soil samples from Cerrado. In addition, a high amount of actinomycete cells was observed in the farms.…”
Section: Biological Indicators Of Soil Qualitysupporting
confidence: 90%
See 3 more Smart Citations
“…Viable bacterial cells counts were higher than those of actinomycete and fungi regardless of the soybean farm, sample collection points, soil depth, and season (Tables 3 to 5). These results are similar to those obtained by Silva et al (2018) in soil samples from Cerrado. In addition, a high amount of actinomycete cells was observed in the farms.…”
Section: Biological Indicators Of Soil Qualitysupporting
confidence: 90%
“…In these farms, bacterial diversity was greater than that of fungi, which confirms the results of viable cell counts (Tables 2 to 4) and Silva et al (2018). This author analyzed the microbial communities in the soil with native vegetation cover.…”
Section: Biological Indicators Of Soil Qualitysupporting
confidence: 81%
See 2 more Smart Citations
“…Plate count analysis carried out on soil samples showed that TMA levels were, on average, in the range 6.7-7.5 Log CFU per g dw. These levels characterize commonly uncultivated soils [59,60]. In general, TMA decreased with depth and this finding is imputed to nutrient and oxygen limitations [61].…”
Section: Discussionmentioning
confidence: 99%